Cardinal Woodpecker creeping on a tree trunk - Kerr, Jeremy (Université d'Ottawa | University of Ottawa, 2019)
This bird was observed at Pretoriuskop camp in Kruger National Park. Bird diversity in protected areas like Kruger is so high that even a casual walk around a camp can reveal remarkable numbers of species. This cardinal woodpecker (_Dendropicos fuscescens_) is common in sub-Saharan Africa but was striking in the bright sun. The red nape behind the head suggests that this is likely a male woodpecker.
Keywords: Cardinal Woodpecker; woodpecker; tree; Africa; African Ecology; South Africa; Kruger National Park